Impact of Dividend Policy on Financial Performance - A Study - Das, Pradip Kumar (Australian Finance & Banking Review, 2020)
This study is an attempt to evaluate the impact of dividend policy on financial performance of selected companies registered in Bombay Stock Exchange. The study based on correlation matrix and panel regression model shows that the selected companies do not follow consistent pattern of dividend payments and the association between price earnings ratio and dividend payout ratio is low positive. However, there is strong association between return on assets and return on equity. Hausman Test reveals that random affect model is appropriate thereby indicating that performance of selected companies have momentous impact on dividend policy. Divided policy is still contemplated as one of the complicated areas in corporate finance. The findings from this study are worthwhile to be welcomed into account by the board of managers of companies to demonstrate dividend policy for the companies.